Свадебные сады: генезис и символика - Бальсис, Римантас; Balsys, Rimantas (Східноєвропейський національний університет імені Лесі Українки, 2016)
В литовской литературе по этнологии вопрос о происхождении свадебного сада не был тщательно проанализирован, а его символика вызывает разные и даже противоречивые мнения. Имеющийся собранный этнографический и фольклорный материал литовского и соседних народов и проведенный его сравнительный анализ, античные мифы позволяют сделать предположение о том, что свадебный сад связан с культом дерева, с антропоморфическим пониманием дерева в древнем мировосприятии, выражающимся в отождествлении человека и дерева. Aнтичные мифы показывают, что деревья (особенно вечные, т. е. цветущие и зимой и летом) были мифологизированы уже в самой древней культуре. В зависимости от среды обитания, климата и образа жизни разные народы мифологизировали разные растения, однако все они выражали ту же символику плодородия, плодовитости, новой жизни. Таким же символом считается и литовский свадебный сад, который до XIX в., а кое-где и до начала XX в. сохранил архаичный вид (украшенная зеленью, бумажками верхушка или ветка елки). С конца XIX в. известен свадебный сад другого вида – многоугольник из соломы. Материалы этих садов отличаются, однако символическое их значение (гарантировать молодым всестороннее плодородие) остается тем же. В XXI в. сады, по словам самих плетельщиков, стали символом дома, сада, родного гнезда, в которое мы возвращаемся и которые охраняют души умерших предков, связи между будущим и прошлым (между поколениями), мостом между новым и старым, на свадьбе – символом новой жизни, надежды.Descriptions of a well-known wedding tradition in northern, eastern and south-eastern parts of Lithuania – to create a straw garden and a ritual of buying it by a matchmaker on the wedding day – reach us only from the end of the 19th century. In Lithuanian ethnological literature, the question of the wedding garden genesis basically is not analyzed, and what concerns its symbolism, there are quite different and even conflicting opinions. In this article, basing himself on the ethnographic and folkloric sources of Lithuanians and neighbouring peoples (Latvian, Russian, Belarusian, Polish, Ukrainian, Finnish, and Swedish), as well as a variety of ancient sources the author tries to reveal the beginnings of a wedding garden, and follow the changes of its form and symbolic meanings from antiquity to these days. In the 19th–20th centuries the wedding garden in different places of Lithuania was also known as liktorius, voras, pajonkas, žarondėliai, reketukas, rekėžis, krijelis, širšuonas, dangus, rojus, karulis. The Latvians called it puzurs, the Poles – rozga weselna, wiecha, wienec; the Czechs – strom, stromek; the Bulgarians – iloja; the Slovenes – kroval; the Ukrainians – jelce, gilce, vilce, rizka; the Belarusians – jelce, sady, elka; the Russians – elka, sady, kurnik, devja krasota. In the 20th century, wedding gardens were made only of straw, but according to the data of the ethnographic descriptions of the 19th century in Northern, eastern and Southern Lithuania the wedding garden was made mostly of a fir tree top, decorated with colorful pieces of paper, apples, nuts, berries, and (sometimes) burning candles. In a similar way, in the 19th century the wedding sign was popular in the Slavic lands. For example, in Poland the wedding garden (rózga weswlna) then was a branch (top) of the pine, pear, fir, oak or silver fir decorated with apples. A wedding garden’s analogue in some Russian regions was a devja krasota. Previously it was a fir or birch, decorated with colorful papers, ribbons and attached to the corner of the house, the ridge or the gate pole, then it was a decoration of bands or headgear. These examples allow making an assumption that the wedding garden was connected with the tree cult, an anthropomorphic conception of trees in the old emotional attitude – dentification of a man and tree. Similar paradigms we find in ancient culture – cults of Cybele, Attis, Demeter and Persephone.
Wedding gardens: genesis and symbolism
Keywords: свадебные сады; wedding garden; символика; обычаи; фольклор; symbolics; custom; folklore